2016
DOI: 10.3109/09637486.2016.1144724
|View full text |Cite
|
Sign up to set email alerts
|

Isoflavone metabolism by a collection of lactic acid bacteria and bifidobacteria with biotechnological interest

Abstract: Almost all soy isoflavones exist as glycosides, daidzin, genistin, and glycitin. We analyzed the capacity of 92 strains of lactic acid bacteria (LAB) and bifidobacteria with biotechnological interest to process the glycosylated isoflavones daidzin, genistin, and glycitin in their more bioavailable aglycones and their metabolites as dihydrodaidzein (DHD), O-desmethylangolensin, and equol. Representative strains of the four genera studied Lactobacillus, Enterococcus, Lactococcus, and Bifidobacterium were able to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(34 citation statements)
references
References 31 publications
2
32
0
Order By: Relevance
“…Gaya et al () investigated the biotransformation of soy extracts and verified that isoflavones metabolism is limited to hydrolysis of glycosidic forms by most of probiotic strains. The authors reported that bifidobacteria and lactic acid bacteria, such as Lactobacillus , have more affinity for conversion of genistin into genistein.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Gaya et al () investigated the biotransformation of soy extracts and verified that isoflavones metabolism is limited to hydrolysis of glycosidic forms by most of probiotic strains. The authors reported that bifidobacteria and lactic acid bacteria, such as Lactobacillus , have more affinity for conversion of genistin into genistein.…”
Section: Resultsmentioning
confidence: 99%
“…Biotransformation of glycoside isoflavones into aglycone forms is relevant since aglycones are compounds with more bioactivity, directly associated with higher bioavailability. Besides that, aglycones can generate metabolites, such as O ‐desmethylangolensin and equol (Gaya et al, ; Selma et al, ; Setchell et al, ). In the present work, equol metabolite was not identified.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In a previous study, Ruiz-Larrea et al (30) reported that genistein presented a highest antioxidant activity comparing to other isoflavones (daidzein, daidzin and genistin) utilizing ABTS method. Fur-thermore, several attempts have been made to improve bioavailability of isoflavone aglycones from isoflavone glycosides in soya beverage milk by fermentation with lactobacilli and bifidobacteria species and large differences in the deglycosylation ability of these bacteria have been reported by several author (5,8,28,31,32). The microorganisms used in the current work can synthesize β-glycosidase which is responsible for removing the sugar moiety from glycosylated isoflavones (5,9,18).…”
Section: Sift Deskmentioning
confidence: 93%